THE EFFECT OF FINANCIAL KNOWLEDGE AND THE USE OF E-MONEY TOWARD FINANCIAL BEHAVIOR OF UNDERGRADUATE STUDENTS FACULTY OF ECONOMICS YOGYAKARTA STATE UNIVERSITY - Safitri, Meyliana; Sari, Ratna Candra (Nominal: Barometer Riset Akuntansi dan Manajemen, 2021)
Abstract: The Effect of Financial Knowledge and The Use of E-Money Toward Financial Behavior of Undergraduate Students Faculty of Economics Yogyakarta State University. This study aims to determine the influence of (1) Financial knowledge toward financial behavior of undergraduate students Faculty of Economics, Yogyakarta State University. (2) Knowing the influence of the use of e-money toward financial behavior of undergraduate students Faculty of Economics, Yogyakarta State University. This research was comparative causal study. The study sample was 217 respondents of the Faculty of Economics, Yogyakarta State University students. Samples were taken using purposive sampling technique. The data analysis technique used is multiple linear regression analysis test. The result of this study show that (1) Financial knowledge has a positive effect on financial behavior of undergraduate students Faculty of Economics, Yogyakarta State University. (2) The use of E-money has a negative effect on financial behavior of undergraduate students Faculty of Economics, Yogyakarta State University. Keywords: Financial Knowledge, E-money, Financial BehaviorAbstrak: Pengaruh Pengetahuan Keuangan, Dan Penggunaan E-Money Terhadap Perilaku Keuangan Mahasiswa S1 Fakultas Ekonomi Universitas Negeri Yogyakarta. Penelitian ini bertujuan untuk mengetahui pengaruh (1) pengetahuan keuangan terhadap perilaku keuangan mahasiswa S1 Fakultas Ekonomi Universitas Negeri Yogyakarta. (2) Mengetahui pengaruh penggunaan e-money terhadap perilaku keuangan mahasiswa S1 Fakultas Ekonomi Universitas Negeri Yogyakarta. Penelitian ini merupakan penelitian hubungan kausal. Sampel penelitian ini adalah 217 responden mahasiswa Fakultas Ekonomi Universitas Negeri Yogyakarta. Sampel diambil menggunakan teknik purposive sampling. Teknik analisis data menggunakan uji analisis regresi linear berganda. Hasil penelitian menunjukan bahwa (1) Pengetahuan Keuangan, berpengaruh positif terhadap Perilaku Keuangan Mahasiswa S1 Fakultas Ekonomi Univeristas Negeri Yogyakarta. (2) Penggunaan e-money berpengaruh negatif terhadap perilaku keuangan mahasiswa S1 Fakultas Ekonomi Universitas Negeri Yogyakarta.Kata kunci: Pengetahuan Keuangan, E-money, Perilaku Keuangan.